Youth Entrepreneurship and Digital Innovation in The Creative Economy - Abdullah, Akmal; Daud, Ahmad; Sumarni, Sumarni; Fitriany, Fitriany (Eastasouth Institute, 2025)
Youth entrepreneurship has emerged as a driving force in Indonesia’s creative economy, particularly as digital innovation continues to transform business models and market opportunities. This study quantitatively examines the influence of digital innovation on entrepreneurial performance among young entrepreneurs operating within various creative subsectors. Using a sample of 120 respondents recruited through purposive sampling, data were collected via structured questionnaires and analyzed using SPSS version 25. Descriptive analysis, validity and reliability testing, and multiple regression were employed to evaluate the relationships among key variables. The results indicate that digital innovation significantly enhances entrepreneurial performance, particularly through improved market reach, operational efficiency, and product differentiation. Furthermore, the findings reveal that digital tools and platforms play a mediating role in strengthening business sustainability among youth-led creative enterprises. This research contributes empirical evidence to the growing literature on digital entrepreneurship in emerging economies and provides practical implications for policymakers, incubators, and educational institutions seeking to foster digitally empowered young entrepreneurs in Indonesia.